(untitled) (Research, Society and Development, 2022)
Objective: To associate socio demographic, anthropometric-nutritional, lifestyle, clinical and obstetric factors of low- and high-risk pregnant women with the weight of the newborn. Methods: A cross-sectional, case series study with 103 pregnant women from a teaching hospital in Recife, Pernambuco, Brazil. Newborn weight was classified as small for gestational age (<P10), adequate for gestational age (p>10 and <90) and large for gestational age (p>90). For statistical analysis, Pearson’s chi-square and Fisher’s exact tests were applied. Results: There was a significant association between gestational risk and newborn weight, with a higher percentage of low-risk pregnant women (62.1%). Among the anthropometric variables, only the weight gain of the pregnant woman showed no significant association with the weight of the newborn. Women with small-for-gestational-age infants had a pre-gestational body mass index of 21.35 kg/m2 and at the end of pregnancy of 26.34 kg/m2, while those with large-for-gestational-age infants had a pre-gestational rate of 31.85 kg/m2, at the end of pregnancy of 36.72 kg/m2 and a higher proportion of overweight 30%, and obesity 60%, by the pre-gestational index, in addition to obesity at the end of pregnancy 70%. Conclusions: There was a significant association between pre-gestational and gestational nutritional status and gestational risk, with birth weight, demonstrating the importance of clinical condition and maternal nutritional status on perinatal outcomes.